Since 6 is positive, it's (x+blank)^2
6/2=3, and (x+3)^2 = x^2+6x+9. We have x^2+6x-2, so we have to add 9 to both sides to get (x+3)^2-2=9, then subtract 9 from both sides to get
(x+3)^2-11=0, or (x+3)^2=11. Square root both sides to get x+3=sqrt(11), and x=sqrt(11)-3, which is approximately 0.32
What you would do is you would substitute each ordered pair into their respective variables. (ie. for (0,1) you would put 0 where the x is and 1 where the y is) You would then solve the equation. If the equation is not even (ie. 2=5 would not be even but 4=4 would be), you move on to the next ordered pair.
If you follow the process right and you get the equations correct, the answer should be B. (7,-2)
Bearing in mind that an absolute value expression is in effect a
piece-wise function with two cases, thus
Answer:
already in standard form
Step-by-step explanation:
the equation of a quadratic in standard form is
y = ax² + bx + c ( a ≠ 0 )
y = x² + 4x + 3 ← is in standard form
with a = 1 , b = 4 , c = 3
Answer:
B=10
Step-by-step explanation:
It's a perfect square of equation ax²+2abx+b²
I'm the given equation a is 1 and b is 5 so 2(a)(b)=2(1)(5)=10
(ps: when I say b in the explanation I mean another b not the one in question as to not be confused)